2000
DOI: 10.1007/s10434-000-0150-6
|View full text |Cite
|
Sign up to set email alerts
|

Women?s Regrets After Bilateral Prophylactic Mastectomy

Abstract: Although a PM statistically reduces the chances of a woman developing breast cancer, the possibility of significant physical and psychological sequelae remains. Careful evaluation, education, and support both before and after the procedure will potentially reduce the level of distress and dissatisfaction in these women. We discuss recommendations for the appropriate surgical and psychiatric evaluation of women who are considering a PM as risk-reducing surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 10 publications
1
57
0
1
Order By: Relevance
“…Ziarnowski et al (2009) found that anticipated regret played an important role in the decision to vaccinate adolescent girls against HPV. Furthermore, several studies highlighted that regret can be experienced by patients before or after cancer-related decisions (e.g., Hu et al, 2003, Montgomery et al, 1999, Clark et al 2001, 2003, Payne et al 2000, and Joseph-Williams et al, 2010.…”
Section: These Studies Base Their Analysis On the Linear-in-parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Ziarnowski et al (2009) found that anticipated regret played an important role in the decision to vaccinate adolescent girls against HPV. Furthermore, several studies highlighted that regret can be experienced by patients before or after cancer-related decisions (e.g., Hu et al, 2003, Montgomery et al, 1999, Clark et al 2001, 2003, Payne et al 2000, and Joseph-Williams et al, 2010.…”
Section: These Studies Base Their Analysis On the Linear-in-parametermentioning
confidence: 99%
“…Ziarnowski et al (2009) found that anticipated regret played an important role in the decision to vaccinate adolescent girls against HPV. Furthermore, several studies highlighted that regret can be experienced by patients before or after cancer-related decisions (e.g., Hu et al, 2003, Montgomery et al, 1999, Clark et al 2001, 2003, Payne et al 2000, and Joseph-Williams et al, 2010.2 The idea that regret is an important determinant of choice behaviour is not new and is well established theoretically and empirically in many fields, including marketing (e.g. Simonson, 1992;Zeelenberg and Pieters, 2007), microeconomics (e.g.…”
mentioning
confidence: 99%
“…Studies have shown that up to half of women who undergo RRM report a negative impact on their sexual relationship [11,12,10], a quarter to one-third report poorer body image and reduced feelings of femininity [12,10], and women are more likely to report feelings of regret related to their surgery when body image and sexual function are adversely affected by RRM [13]. Despite this, few women who undergo RRM report that they regret their surgery decision [14,15,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, an important predictor of a patient later regretting having had PM is when the physician was the one to introduce this option into the discussion of treatment [6,45]. This emphasizes that physicians must be well aware of how much they may influence a woman's decision to have prophylactic surgery, and they must remain alert when giving advice about possible treatment and monitoring options and verify whether the choice for prophylactic surgery is based on the patients' own decision.…”
Section: Screening For Cancermentioning
confidence: 99%